Extracellular Vesicles and Renal Fibrosis: An Odyssey toward a New Therapeutic Approach - Kosanović, Maja (Int J Mol Sci, 2021)
Renal fibrosis is a complex disorder characterized by the destruction of kidney parenchyma. There is currently no cure for this devastating condition. Extracellular vesicles (EVs) are membranous vesicles released from cells in both physiological and diseased states. Given their fundamental role in transferring biomolecules to recipient cells and their ability to cross biological barriers, EVs have been widely investigated as potential cell-free therapeutic agents. In this review, we provide an overview of EVs, focusing on their functional role in renal fibrosis and signaling messengers responsible for EV-mediated crosstalk between various renal compartments. We explore recent findings regarding the renoprotective effect of EVs and their use as therapeutic agents in renal fibrosis. We also highlight advantages and future perspectives of the therapeutic applications of EVs in renal diseases.